Mediating role of organizational creativity between employees' intention in knowledge management process and organizational performance: An empirical study on pharmaceutical employees - Hira Riaz; Atif Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Companies try to putefforts in upgrading the intellectual capital and leveraging them to develop and sustain competitive advantage in the business.Considering this view, thestudy unpacks the relation between knowledge management process (KMP) and organizational performancewith the mediation effect of organizational creativity. The employees/users of this system havea pivotal role in the success of the process. This studyencompasses the literature by examiningthe impact of knowledge management process (creation, storage,transfer, usage) from user perspective and study the process with the intention of employees involving to create new products/services to improve organizational performance in the context of Pakistani region. Quantitative research strategy was used and data collectedfrom respondents via survey technique from Pharmaceutical organizations with a sample size of 203 employees. Structural equation modelingwas used to check the causal relationship and Haye's process was applied for mediation test. It appeared that organizational creativity plays a mediation role and leadstowards invigorating organizational performance. Pharmaceutical professionals should considerthat employees' intentions towards KMP are critical to serve the purpose of the system. This research reveals the significance of user intention in KMP and add value to the literature in the context of Pakistan's pharmaceutical sector.
Keywords: 330; knowledge management process; knowledge creation; knowledge sharing; knowledge usage; pharmaceutical sector